Islam mengentaskan kemiskinan. Tinjauan kritis, analisis tentang hadist ekonomi - ALBANI, Muhammad Nashiruddin (Pustaka Azam, 2002)
Islam mengentaskan kemiskinan. Tinjauan kritis, analisis tentang hadist ekonomi